DE LA IMPRENTA MANUAL A LA MECÁNICA: PRIMEROS INTENTOS DE CAMBIO EN ESPAÑA - Fermín de los Reyes Gómez (Cuadernos de Ilustración y Romanticismo)
The change from manual to mechanical printing was gradual and took place between the end of the eighteenth century and the first decades of the nineteenth century, being the latter the years that marked the transition. We know the main technical innovations made in other countries which arrived to Spain through publications or industrial espionage, but we are not aware that, in our country, there were several private and official attempts to improve the printing press, typography and typesetting. In this article, I show several of these attempts, their descriptions and even pictures of their devices. For several reasons they did not succeed, but some could have pioneered European mechanical printing.